Direct Health Education Effect on Mandangin Island Public's Knowledge of The Most Common Diseases in Children - Athiyyah, Alpha Fardah; Ranuh, Reza Gunadi; Darma, Andy; Puspitasari, Dwiyanti; Sumitro, Khadijah Rizky; Faizi, Muhammad; Sudarmo, Subijanto Marto (Journal of Community Medicine and Public Health Research, 2023)
Pneumonia, diarrhea, and other infectious diseases are some of the most common diseases found in children. Although preventable, the morbidity and mortality rate in children caused by these common diseases are relatively high, and the poor regions are disproportionally affected. Comprehensive health education for adults and parents can effectively prevent these common diseases, especially in remote areas. This study aimed to determine the effect of health education as community development program from the Gastroenterology Division of the Department of Child Health Faculty of Medicine Universitas Airlangga on Mandangin Island public's knowledge about the most common diseases in children. This cross-sectional study was conducted on 61 subjects from Mandangin Island on 4th October 2022. The subjects were assessed on their characteristics and given a pre- and post-health education questionnaire to evaluate their knowledge. The questionnaire was composed of five questions with a minimum score of 0 and a maximum of 100. Results from the pre- and post-test questionnaires were compared using the Paired T-Test method and processed with SPSS; p <0.05 was considered significant. There was a significant increase in public knowledge about the most common diseases in children with a p-value of 0.002 (64.26±31.44; 76.9±22.63). These findings support the importance of health education in the public's knowledge of the most common diseases in children.